DISTRIBUTION OF CATCHES IN THE FISHING PORT OF PALABUHANRATU SUKABUMI, WEST JAVA - Simbolon, Veronika; Yani, Alit Hindri; Hutauruk, Ronal Mangasi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis research was conducted in 2018 at the Port of Fisheries in Palabuhanratu, Sukabumi, West Java. This study aims to determine the distribution of how the distribution of fishermen's catches landed at PPN Palabuhanratu. One of the functions of the fishing port is as a center for marketing and distributing catches. Palabuhanratu is a fairly large port in West Java and has the potential in the distribution of catches. Palabuhanratu Fishery Port is the center of fisheries activities, especially in the aspects of production, processing, distribution and fostering fishing communities. The distribution of catches at the Port of Palabuhanratu Fisheries has several important aspects including catching landing, managing and marketing the catch. Marketing of fishery products from the Port of Palabuhanratu Fisheries in the form of fresh fish and processed fish products (salted and pindang fish). Distribution destinations include Palabuhanratu (local) and inter-city distribution including Sukabumi, Jakarta, Bandung, Bogor, Cicurug and Cianjur. The destination areas for distribution between provinces include Banten and Surabaya. The distribution of catches is carried out to give value to the catches.The value of the catch that is distributed is very dependent on the quality of the catch.Palabuhanratu has two forms of marketing activities namely through TPI and not through TPI. The fish which are marketed through TPI are not auctioned properly because the fish auction in Palabuhanratu has not gone well. Keywords : Fishing Port, Distribution of catches, marketing the catch